Effects of the Rulings of Constitutional Court in Time - Pūraitė-Andrikienė, Dovilė (Teisė, 2019)
The article analyzes the temporal effects of the Constitutional Court of the Republic of Lithuania’s rulings, i.e., ex tunc, ex nunc, and pro futuro elements of judicial decisions in the constitutional justice model of Lithuania. This article aims to reveal the development of the doctrine of exceptions of the constitutionaly established rule, that the force of the decisions of the Constitutional Court is directed to the future, in the jurisprudence of a Constitutional Court and further development of this institute inter alia in light of the 2019 amendment to the Constitution of the Republic of Lithuania, which introduced a mechanism for lodging an individual constitutional complaint.